Measuring the Status of IPO Knowledge among University Teachers - Gurung, Jas Bahadur (Prithvi Journal of Research and Innovation, 2019)
This study surveys 118 university teachers to assess their initial public offering (IPO) knowledge. Percentage, mean, standard deviation, chi-square test and one way ANOVA have been used in carrying out analysis of the data. Results show that most of the university teachers have moderate level of IPO knowledge but they lack in attending formal courses or trainings in IPO activities. A one way ANOVA result indicates that there is insignificant effect of types of academic institutions viz. private, public and constituent on IPO knowledge among university teachers at 5 percent level of significance. Furthermore, the study reveals that university teachers are highly influenced and guided towards IPO activities by their self-awareness followed by media, publications, friends and their job experiences.